Material and Operations Sustainability: An Approach towards Make in India - Mangla, Sachin Kumar; Patil, Pravin P. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*297.67px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944571);" role="presentation">This special issue of the <span dir="ltr" style="left: calc(var(--scale-factor)*197.57px); top: calc(var(--scale-factor)*297.67px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.978651);" role="presentation">Journal of Graphic Era University <span dir="ltr" style="left: calc(var(--scale-factor)*374.35px); top: calc(var(--scale-factor)*297.67px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.951576);" role="presentation">is primarily devoted to papers <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*313.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.998455);" role="presentation">from the <span dir="ltr" style="left: calc(var(--scale-factor)*121.94px); top: calc(var(--scale-factor)*313.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.985053);" role="presentation">National Conference on Material and Operations Sustainability: An Approach <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.92178);" role="presentation">towards <span dir="ltr" style="left: calc(var(--scale-factor)*118.22px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.905521);" role="presentation">Make <span dir="ltr" style="left: calc(var(--scale-factor)*152.17px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999572);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*168.96px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.973933);" role="presentation">India, <span dir="ltr" style="left: calc(var(--scale-factor)*204.64px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.954368);" role="presentation">which <span dir="ltr" style="left: calc(var(--scale-factor)*241.35px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.87104);" role="presentation">was <span dir="ltr" style="left: calc(var(--scale-factor)*267.37px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.954681);" role="presentation">successfully held <span dir="ltr" style="left: calc(var(--scale-factor)*361.41px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.8616);" role="presentation">at <span dir="ltr" style="left: calc(var(--scale-factor)*377.47px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*399.54px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917496);" role="presentation">Graphic <span dir="ltr" style="left: calc(var(--scale-factor)*445.60px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.889555);" role="presentation">Era <span dir="ltr" style="left: calc(var(--scale-factor)*469.59px); top: calc(var(--scale-factor)*329.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.972932);" role="presentation">University, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.913648);" role="presentation">Dehradun, India on August 22-<span dir="ltr" style="left: calc(var(--scale-factor)*221.69px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89982);" role="presentation">23, 2016. <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*376.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.942696);" role="presentation">Currently, Manufacturing and <span dir="ltr" style="left: calc(var(--scale-factor)*220.97px); top: calc(var(--scale-factor)*376.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925428);" role="presentation">Industrial Engineering Managem<span dir="ltr" style="left: calc(var(--scale-factor)*381.07px); top: calc(var(--scale-factor)*376.99px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908615);" role="presentation">ent scholars and practitioners <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*392.83px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907965);" role="presentation">are facing new challenges in integrating issues of manufacturing and operations management <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*408.79px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925192);" role="presentation">with their conventional areas of interest. There is an increasing concern for industry in terms <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*424.63px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.952876);" role="presentation">of material selection, material proper<span dir="ltr" style="left: calc(var(--scale-factor)*256.97px); top: calc(var(--scale-factor)*424.63px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.924756);" role="presentation">ties and its structure, operations sequence, operations <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*440.47px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.905517);" role="presentation">optimization, process performances etc. In recent years, there has been a growing awareness <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*456.33px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.962524);" role="presentation">and pressure on industries to inculcate ecological concerns and nature friendly means in <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*472.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.977581);" role="presentation">business with a sus<span dir="ltr" style="left: calc(var(--scale-factor)*173.78px); top: calc(var(--scale-factor)*472.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00985);" role="presentation">tainability orientation. Sustainability involves fulfilling the needs of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*488.13px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.966726);" role="presentation">present without compromising the needs of the future. By virtue of which, academicians, <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.850513);" role="presentation">researchers <span dir="ltr" style="left: calc(var(--scale-factor)*133.43px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*158.36px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.91795);" role="presentation">practitioners <span dir="ltr" style="left: calc(var(--scale-factor)*225.88px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.995171);" role="presentation">all <span dir="ltr" style="left: calc(var(--scale-factor)*245.53px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.890924);" role="presentation">around <span dir="ltr" style="left: calc(var(--scale-factor)*286.32px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*308.74px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.974059);" role="presentation">world <span dir="ltr" style="left: calc(var(--scale-factor)*344.24px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.846367);" role="presentation">are <span dir="ltr" style="left: calc(var(--scale-factor)*366.42px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.965052);" role="presentation">talking <span dir="ltr" style="left: calc(var(--scale-factor)*407.44px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.890503);" role="presentation">about <span dir="ltr" style="left: calc(var(--scale-factor)*441.73px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93411);" role="presentation">sustainability <span dir="ltr" style="left: calc(var(--scale-factor)*513.20px); top: calc(var(--scale-factor)*503.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*519.81px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.869666);" role="presentation">resource<span dir="ltr" style="left: calc(var(--scale-factor)*112.58px); top: calc(var(--scale-factor)*519.81px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.906964);" role="presentation">s, material, operations and processes for sustainable development initiatives from the <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.943857);" role="presentation">industrial <span dir="ltr" style="left: calc(var(--scale-factor)*125.76px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.890167);" role="presentation">perspective. <span dir="ltr" style="left: calc(var(--scale-factor)*191.84px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">Thus, <span dir="ltr" style="left: calc(var(--scale-factor)*227.23px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.875201);" role="presentation">there <span dir="ltr" style="left: calc(var(--scale-factor)*259.61px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.923183);" role="presentation">is <span dir="ltr" style="left: calc(var(--scale-factor)*276.04px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.845577);" role="presentation">an <span dir="ltr" style="left: calc(var(--scale-factor)*295.81px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902205);" role="presentation">urgent <span dir="ltr" style="left: calc(var(--scale-factor)*334.91px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.845577);" role="presentation">need <span dir="ltr" style="left: calc(var(--scale-factor)*365.96px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999429);" role="presentation">for <span dir="ltr" style="left: calc(var(--scale-factor)*388.38px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93106);" role="presentation">transition <span dir="ltr" style="left: calc(var(--scale-factor)*442.12px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.969);" role="presentation">from <span dir="ltr" style="left: calc(var(--scale-factor)*473.78px); top: calc(var(--scale-factor)*535.65px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.949942);" role="presentation">traditional <span dir="ltr" style="left: calc(var(--scale-factor)*72.02px); top: calc(var(--scale-factor)*551.61px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.890005);" role="presentation">manufacturing and operations management to sustainable operations management.